Predicting chronic postoperative pain after total knee replacement surgery in patients with knee osteoarthritis - Kurien, Thomas (2018)
We hypothesise that preoperative pain characteristics in knee osteoarthritis (OA) patients may explain persistent pain after total knee replacement (TKR) surgery. Fifty patients awaiting TKR surgery and twenty-two asymptomatic healthy controls were recruited to evaluate the degree of neuropathic pain symptoms and central sensitisation of pain. OA patients were pain phenotyped into two groups based on the PainDETECT questionnaire: Group-A (scores ≥19) indicating neuropathic pain-like symptoms, Group-B (scores <19) indicating nociceptive or mixed pain. Controls were assigned to Group-C. Cuff algometry assessing pain detection thresholds (PDT) and pain tolerance (PTT) was conducted on the lower legs. Temporal summation of pain (TSP) was assessed using ten sequential cuff stimulations set at the subject's individual PTT and a von Frey stimulator. Conditioning pain modulation (CPM) was assessed by cuff pain conditioning on one leg and parallel assessment of PDT on the contralateral leg. Pressure pain thresholds (PPTs) were recorded by pressure handheld algometry local and distant to the knee. Knee pain intensity assessed using the visual analogue scale (VAS score (0-10cm) as well as questionnaires to assess knee function, depression, anxiety, pain catastrophizing and quality of life were collected before and 6 months post-TKR.